Bimbingan Teknis Pembuatan Proposal Kredit Dan Laporan Keuangan UMKM Beken Kabupaten BekasI - Adibah Adibah; Siska Wulandari; Rina Nurjanah; Arief Teguh Nugroho (Pengelola Jurnal Politeknik Negeri Ketapang, 2022)
Technical guidance activities for credit proposals and financial reports are carried out to increase the entrepreneurial skills of business actors, especially MSMEs (Micro, Small and Medium Enterprises). This activity refers to follow-up activities for the establishment of well-known MSMEs (Bekasi Keren/Bekasi Regency). Bimtek activities are one way to increase the ability of MSMEs to increase their potential and become superior MSMEs, not only from the products produced but from the literacy/knowledge they possess. This activity was carried out in collaboration with the MSMEs, and Cooperative Service as well as Pelita Bangsa University. The implementation time will be 11-14 October 2021 at the Java Palace Hotel Jababeka. The participants of the activity amounted to 200 (two hundred) MSMEs participants. The material presented is in the form of a credit application proposal and the preparation of financial reports. The output of technical guidance is in the form of an assessment on the post-test which is carried out after the training is held. For credit application proposal materials and financial reports, 106 respondents filled out the post-test link with a score of 60-100 as many as 91% or 91 participants, while 9% got a score of 0-50 or as many as 9 people. It can be concluded that the level of understanding of the material is very well received by the participants of the technical guidance